Unlocking The Outlook Of The Halal Industry Through Islamic Financial Instruments - Achmad Nur Alfianto (Al-Mashrof: Islamic Banking and Finance, 2025)
The rapid development of the global halal industry presents a strategic opportunity to strengthen its integration with Islamic finance, as both sectors operate under shared Shariah principles. However, existing research shows a limited availability of practical frameworks that explain how such integration can be applied along the halal value chain. This study aims to formulate a conceptual model for integrating Islamic finance within halal industry operations. Using a qualitative, library-based approach, this research reviews peer-reviewed publications retrieved through academic databases using keywords related to halal industry and Islamic finance integration. The findings propose a two-dimensional integration model: (1) Shariah-compliant financing schemes - including Islamic banking, sukuk, and alternative Islamic financial instruments - and (2) operational financial services such as payroll systems, digital payments, and integrated financial management solutions. The model illustrates how Islamic financial institutions can support halal industry actors in ensuring that both funding sources and financial operations comply with Shariah requirements. The study suggests the need for policymakers to strengthen standards and audit mechanisms, encourages halal industry practitioners to adopt Islamic financial services comprehensively, and highlights the importance of product innovation among Islamic financial institutions to build an integrated halal economic ecosystem. Keywords: Halal Industry, Islamic Finance, Financing Adoption